Wavelength-accurate and wafer-scale process for nonlinear frequency mixers in thin-film lithium niobate - C. J. Xin; Shengyuan Lu; Jiayu Yang; Amirhassan Shams-Ansari; Boris Desiatov; Letícia S. Magalhães; Soumya S. Ghosh; Erin McGee; Dylan Renaud; Nicholas Achuthan; Arseniy Zvyagintsev; David Barton III; et al. (Communications Physics)
Abstract Recent advancements in thin-film lithium niobate (TFLN) photonics have led to a new generation of high-performance electro-optic devices, including modulators, frequency combs, and microwave-to-optical transducers. However, the broader adoption of TFLN-based devices that rely on all-optical nonlinearities have been limited by the sensitivity of quasi-phase matching (QPM), realized via ferroelectric poling, to fabrication tolerances. Here, we propose a scalable fabrication process aimed at improving the wavelength-accuracy of optical frequency mixers in TFLN. In contrast to the conventional pole-before-etch approach, we first define the waveguide in TFLN and then perform ferroelectric poling. This sequence allows for precise metrology before and after waveguide definition to fully capture the geometry imperfections. Systematic errors can also be calibrated by measuring a subset of devices to fine-tune the QPM design for remaining devices on the wafer. Using this method, we fabricated a large number of second harmonic generation devices aimed at generating 737 nm light, with 73% operating within 5 nm of the target wavelength. Furthermore, we also demonstrate thermo-optic tuning and trimming of the devices via cladding deposition, with the former bringing ~96% of tested devices to the target wavelength.